(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article considers the issues of the formation of communicative competence in the lessons of the Russian language. The author of the article argues that innovative pedagogical technologies used to form communicative competence develop creative activity, form mental activity, teach students to defend their point of view, and help to achieve a deep understanding of the material.